Color analysis of horticultural produces using hue spectra fingerprinting - Lien Le Phuong Nguyen (Elsevier, 2021)
Color has great importance in agriculture due to its relationship with plant pigments and therefore, plant development and biochemical changes. Due to the trichromatic vision, instruments equipped with CCD or CMOS sensor represent color with the mixture of red, green and blue signals. These values are often transformed into HSL (hue, saturation, luminance) color space. Beyond average color of the visible surface area, histograms can represent color distribution. Interpretation of distribution can be challenging due to the information shared among histograms. Hue spectra fingerprinting offers color information suitable for analysis with common chemometric methods and easy to understand. Algorithm is presented with GNU Octave code. • Hue spectra is a histogram of hue angle over the captured scene but summarizes saturation instead of number of pixels. There are peaks of important colors, while others of low saturation disappear. Neutral backgrounds such as white, black or gray, are removed without the need of segmentation. • Color changes of fruits and vegetables are represented by displacement of color peaks. Since saturation is usually changing during ripening, storage and shelf life, peaks also change their shape by means of peak value and width.